Produzione di senso a mezzo di oggetti. Cristallizzazioni dell’umano - Adolfo Fattori (Im@go. A Journal of the Social Imaginary, 2019)
The Production of Meaning by Means of Things. We live surrounded by things. Objects that are imagined, designed, built by us to achieve our weakness and inadequacy to survive with only our strenght and body. We build prosthesis to increase our strenght and things to ensure comfort in our daily life. Objects communicate with us, and beetwen them, and crystallize inside them the meanings we give them. .Some of major scholars have studied the relations between things and us: Georg Simmel, Walter Benjamin, Arnold Gehlen, Jean Baudrillard Roland Barthes, Louis Bolke, Abraham Moles, Jan Mukařovský too. This essays aims at exploring the above mentioned issues.